Ḍô. Ketakarāñcẽ sānnidhya : Ketakar̃āsambandh̃ī lekhasaṅgraha, arthāt, guṇadoshavivecaka alpacaritra - Dāte, Yaśavanta Rāmakrshṇa, 1891- (SAMP early 20th-century Indian books project ;, 1946)
Biography of Shridhar Venkatesh Ketkar, 1884-1937, Marathi author.